2004
DOI: 10.1111/j.1399-543x.2004.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle lipid accumulation in obesity, insulin resistance, and type 2 diabetes

Abstract: In addition to obesity, many factors, including the distribution of body fat, contribute to the development of insulin resistance and type 2 diabetes mellitus (T2DM). Lipid contained within skeletal muscle as triglyceride is a parameter of regional fat accumulation thought to be an important link among obesity, insulin resistance, and type 2 diabetes, even in the pediatric population. Intramuscular triglycerides can also be a fuel source for healthy muscle during periods of physical activity. Thus, the balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
140
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 97 publications
4
140
1
4
Order By: Relevance
“…4 Although IMCL is purportedly influenced by diet and exercise; studies also report strong correlations between IMCL and insulin resistance irrespective of diet, age, weight, activity level and gender. 5 Nevertheless, in our study, while gender, body weight, physical activity and age were well controlled, elevations in myocellular lipids (3.3 (IMCL) and 4.5 (EMCL) times elevation relative to controls) are far greater than those attributable to dietary influences (0.32 times elevation in previous dietary studies). 4 The highly elevated IMCL levels in the incomplete SCI group in this study raises concern because of their reported association with insulin resistance in sedentary individuals with normal body weights as well as obese individuals.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…4 Although IMCL is purportedly influenced by diet and exercise; studies also report strong correlations between IMCL and insulin resistance irrespective of diet, age, weight, activity level and gender. 5 Nevertheless, in our study, while gender, body weight, physical activity and age were well controlled, elevations in myocellular lipids (3.3 (IMCL) and 4.5 (EMCL) times elevation relative to controls) are far greater than those attributable to dietary influences (0.32 times elevation in previous dietary studies). 4 The highly elevated IMCL levels in the incomplete SCI group in this study raises concern because of their reported association with insulin resistance in sedentary individuals with normal body weights as well as obese individuals.…”
Section: Discussioncontrasting
confidence: 64%
“…6 Moreover, skeletal muscle is the major depot (B80%) for blood glucose and marked muscle atrophy has been shown to be a secondary risk factor for insulin resistance. 5 The combination of muscle atrophy, 1 relative inactivity 8 and high IMCL levels in persons with incomplete SCI potentially renders this patient population particularly vulnerable to altered glucose homeostasis. Accordingly, in the light of recognizing elevated IMCL content as detected by MR measures, our findings suggest that such metabolic adaptations should be assessed in response to the injury as well as different rehabilitation protocols in this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 IMCL content is determined by the balance between the uptake of free fatty acid into skeletal muscle cells and fatty acid b-oxidation within the mitochondria. 10 Thus, abnormal fatty acid metabolism within the mitochondria can reduce the production of energy from fatty acid, which in turn might impair aerobic capacity in MetS. However, the significance of IMCL in the skeletal muscle energy metabolism and aerobic capacity in MetS is not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%